Dialetic Between Islamic Law and Adat Law in the Nusantara: A Reinterpretation of the Terengganu Inscription in the 14th Century - Yakin, Ayang Utriza (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
This article discusses the inscription found in Terengganu, which originated in the early XIV Century. The inscription documents the laws implemented by the rulers of the time. These texts reveal that the laws of this time came from two sources: Islamic law and customary (adat) law. In other words, the inscription indicates that legal pluralism was already in existence by the 14th Century. Adat law was the principle legal system in place, playing an important role in the archipelagic society at the time. However, there was an alternative system of Islamic law (e.g. stoning as a punishment for adultery) in place for lower social classes. This finding suggests that Islamic law was already in existence in the early 14th centuryâmuch earlier than the prevailing understanding of the history of Islamic law suggests. The article contributes by providing the new transliteration from Jawi into Latin characters and the new translation from old-Malay into modern English, which are arguably more accurate than the previous work.